Trion-mediated förster resonance energy transfer and optical gating effect in WS2/hBN/MoSe2 heterojunction - Hu, Zehua (2020)
van der Waals two-dimensional layered heterostructures have recently emerged as a platform, where the interlayer couplings give rise to interesting physics and multifunctionalities in optoelectronics. Such couplings can be rationally controlled by dielectric, separation, and stacking angles, which affect the overall charge or energy-transfer processes, and emergent potential landscape for twistronics. Herein, we report the efficient Förster resonance energy transfer (FRET) in WS2/hBN/MoSe2 heterostructure, probed by both steady-state and time-resolved optical spectroscopy. We clarified the evolution behavior of the electron-hole pairs and free electrons from the trions, that is, ∼59.9% of the electron-hole pairs could transfer into MoSe2 by FRET channels (∼38 ps) while the free electrons accumulate at the WS2/hBN interface to photogate MoSe2. This study presents a clear picture of the FRET process in two-dimensional transition-metal dichalcogenides' heterojunctions, which establishes the scientific foundation for developing the related heterojunction optoelectronic devices.